2018
DOI: 10.1186/s12978-017-0450-y
|View full text |Cite
|
Sign up to set email alerts
|

The CRADLE vital signs alert: qualitative evaluation of a novel device designed for use in pregnancy by healthcare workers in low-resource settings

Abstract: BackgroundVital signs measurement can identify pregnant and postpartum women who require urgent treatment or referral. In low-resource settings, healthcare workers have limited access to accurate vital signs measuring devices suitable for their environment and training. The CRADLE Vital Signs Alert (VSA) is a novel device measuring blood pressure and pulse that is accurate in pregnancy and designed for low-resource settings. Its traffic light early warning system alerts healthcare workers to the need for escal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 34 publications
3
44
0
Order By: Relevance
“…7 Preliminary qualitative studies indicated that both users and patients approved of the device. 8 The ultimate step in the development was determining in the present study whether the use of the device in low-resource centres improved outcomes. The study design was a stepped-wedge, cluster-randomised controlled trial.…”
Section: The Challenge Of Measuring Blood Pressure In Low-resource Sementioning
confidence: 89%
“…7 Preliminary qualitative studies indicated that both users and patients approved of the device. 8 The ultimate step in the development was determining in the present study whether the use of the device in low-resource centres improved outcomes. The study design was a stepped-wedge, cluster-randomised controlled trial.…”
Section: The Challenge Of Measuring Blood Pressure In Low-resource Sementioning
confidence: 89%
“…Previous work in India, Mozambique and South Africa has shown that unskilled community health workers perceive the CRADLE VSA as easy-to-use 14 and it meets the speci c WHO requirements for use in low income settings, being affordable (£15 GBP), robust, portable with low power requirements. 15…”
Section: Discussionmentioning
confidence: 99%
“…Although the current model of the CRADLE VSA does not have mobile health (mHealth) capabilities, incorporation of mHealth technology into future models is feasible, allowing for transmission of vital signs data from the device to mobile phones or directly to a central facility. 75 PIERS on the Move (PotM) is a low-cost, easy-touse, mHealth app that has been developed to aid health workers in making decisions on management of women with preeclampsia. This app is based on a decision model that combines accurate risk prediction of maternal adverse outcomes associated with preeclampsia (miniPIERS), with WHO recommendations for the management of preeclampsia.…”
Section: Innovation and Development Of New Technologies Designed For mentioning
confidence: 99%